2004
DOI: 10.1108/00346650410568336
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxins in Nigerian dry‐roasted groundnuts

Abstract: Samples of dry-roasted groundnuts purchased from street hawkers, markets and retail shops in southwestern Nigeria were analysed for moisture content, fungal populations and aflatoxin contamination. The moisture content varied from 2.1 to 3.6 per cent, while the mould counts using the dilution plating method ranged from 2.9 £ 10 2 to 6.3 £ 10 2 colony-forming units per gram in samples. Aflatoxin B 1 was found in 64.2 per cent of samples with a mean of 25.5 ppb. Aflatoxins B 2, G 1 and G 2 were detected in 26.4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 9 publications
2
22
0
Order By: Relevance
“…() and Bankole et al. () but somewhat similar to levels found in groundnut cake (kulikuli) samples in our previous study (Ezekiel et al. ).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…() and Bankole et al. () but somewhat similar to levels found in groundnut cake (kulikuli) samples in our previous study (Ezekiel et al. ).…”
Section: Discussionsupporting
confidence: 89%
“…roasted groundnut) (Bankole et al. ); hence, the need to continuously monitor the incidence of this toxic natural chemical produced by aflatoxigenic moulds in groundnut. The recovery of propagules of Aspergillus section Flavi species in all groundnut samples and the significantly higher incidence of aflatoxigenic A. flavus species compared to the non‐aflatoxigenic isolates, irrespective of processing method used, supports previous studies which showed that groundnut is highly susceptible to contamination from Aspergillus species (Subrahmanyam et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…conducive to fungal growth and toxin production (Njobeh et al, 2009;Bhattacharya and Raha, 2002;Bankole et al, 2005;Abdel-Gawad and Zohri, 1993). The storage temperature, moisture content, presence of oxygen and gaseous composition are the most important factors influencing the development of fungi during storage in these nut seeds (Ayyasam and Baskaran, 2005).…”
Section: Introductionmentioning
confidence: 99%